Równanie A:
[tex]7x-13 + 3x = 14 +5x +3\\10x - 13 = 5x+17/+13\\10x = 5x+30/-5x\\5x = 30/:5 \\x = 6[/tex]
Równanie B:
[tex]7(2x-1)-(5x-3) = 4\\14x - 4 - 5x=4\\9x-4 = 4/+4\\9x = 8/:9\\x = \frac{8}{9}[/tex]
Równanie C:
[tex]\frac{2x+1}{3}-\ \frac{3x-1}{4}=2-x\\\\\frac{2}{3} x + \frac{1}{3} + \frac{-3}{4} x + \frac{1}{4} = 2x +(-x)\\\\\frac{-1}{12} x + \frac{7}{12} = -x+2 /+x\\\\\frac{11}{12} x + \frac{7}{12} = 2 /-\frac{7}{12} \\\\\frac{11}{12} x = \frac{17}{12} / \cdot\frac{17}{11} \\\\x = \frac{17}{11} = 1\frac{6}{11}[/tex]